Nucleosomes and their complexes in the cryoEM era: Trends and limitations - Armeev, Grigoriy A.; Gribkova, Anna K.; Shaytan, Alexey K. (Frontiers in Molecular Biosciences, 2022)
Twenty-five years have passed since the appearance of the first atomistic model of the nucleosome structure, and since then the number of new structures has gradually increased. With the advent of cryo-microscopy, the rate of accumulation of models has increased significantly. New structures are emerging with different histone variants and a variety of proteins that bind to nucleosomes. At the moment, there are more than four hundred structures containing nucleosomes in the Protein Data Bank. Many of these structures represent similar complexes, others differ in composition, conformation and quality. In this perspective, we investigate the diversity of known nucleosome structures, analyze data and model quality, variations in histone/ DNA content of nucleosomes and spectrum of their interactors. We outline those parts of the nucleosome “structurome” that are already explored and those awaiting further exploration.